De la « maison commune européenne » à la désintégration du pacte de Varsovie... et à celle de l'URSS - Lévesque, Jacques (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1992)
By moving rather belatedly towards a controlled democratization of Eastern Europe's political regimes, Gorbachev and his team sought to carry out a vast and ambitious plan to transform the international order in Europe, a plan which was to yield considerable benefits for the USSR. The process having got out of hand, the USSR did not step in to preserve the objectives of its European policy which, at the same time, was seriously compromised. It attempted to adjust to Eastern Europe's new political situation by making, over more than a year, great efforts to preserve the existence of a transformed and renewed Warsaw Pact, seeing in it an indispensable transitory instrument for its new European policy. The collapse of Eastern Europe's regimes and the progressive disintegration of the Warsaw Pact largely contributed to Gorbachev's losing control of the political situation in the USSR and greatly accelerated its breakup.